ANALISIS KETERAMPILAN DASAR MENGAJAR MAHASISWA PRODI PENDIDIKAN MATEMATIKA SEBAGAI CALON GURU MATEMATIKA PADA MATA KULIAH PENGAJARAN MIKRO [ANALYSIS OF BASIC TEACHING SKILLS OF MATHEMATICS EDUCATION STUDY PROGRAM STUDENTS AS PROSPECTIVE MATHEMATICS TEACHERS IN MIKRO TEACHING COURSES] - Imelda Imelda; Friska Ledina Situngkir (JOHME: Journal of Holistic Mathematics Education)
Basic teaching skills are skills needed by prospective teachers to become effective, efficient and professional teachers. Mathematics Education Study Program students are prepared to become prospective teachers with good basic teaching skills in microteaching courses. Micro teaching requires students to be able to compile lesson plans in the form of lesson plans or teaching modules. Then the lesson plan is practiced in classroom learning. It is during this teaching practice that students demonstrate these basic teaching skills. In theory, students understand the basic skills of teaching. However, what about when practicing. This study aims to describe the basic teaching skills of Mathematics Education Study Program students as prospective Mathematics teachers. The research method is qualitative descriptive. The subjects in this study were 13 students of the Mathematics Education Study Program at Santo Thomas Catholic University, 6th semester students of the 2022/2023 academic year. Data were collected from observation, documentation and interviews. The results of the analysis of the basic teaching skills of prospective Mathematics teachers in the Mathematics Education Study Program include the skills of opening and closing lessons well (4.1), the skills of explaining are quite good (3.95), the skills of asking questions are quite good (3.64), the skills of giving reinforcement are good (4.61), the skills of holding variations are quite good (3.93), the skills of guiding group discussions are quite good (3.93), the skills of managing class and discipline are good (good), the skills of teaching small groups and individuals are quite good (3.7). Thus it can be concluded that there are still some basic teaching skills that need to be improved by students.